Collaborative Governance in the Development of Religious Tourism in Blitar City - Putri, Helma Sofyta; Maharani, Wydha Mustika; Lailin, Ulva Roifatul (Universitas 17 Agustus 1945 Surabaya, 2024)
The tourism sector is one of the economic potentials that must be continuously developed, including in Blitar City which has religious tourism such as Bung Karno's Tomb and the Ar-rahman Mosque. However, several infrastructure and facility problems have arisen, such as the parking of tourism buses on the side of the road which causes congestion around the Ar-Rahman Mosque, and damaged visitor seats at the Bung Karno Tomb. Based on Blitar City Regional Regulation Number 12 of 2011 concerning the 2011-2030 Regional Spatial Plan of Blitar City, Article 57 paragraph 1 states that cultural tourism areas must be managed properly. This study aims to discover the collaboration process in developing religious tourism in Blitar City by using the Ansell and Gash (2008) model approach as the analysis knife. Qualitative methods were used in this study by conducting observations, interviews, and documentation with stakeholders at the Blitar City Culture and Tourism Office, Bung Karno's Tomb, and the Ar-Rahman Mosque. The results showed that collaboration in developing religious tourism involving the government, private sector, and local communities is very important. However, the collaboration process has not been fully by the principles of collaborative governance, especially in building trust and mutual understanding with the management of the Ar-Rahman Mosque. Other collaboration processes, such as face-to-face dialogue and commitment have started to run by producing socialization activities to increase tourism and halal certification program campaigns.